Principles of Problem-Based Learning (PBL) in STEM Education: Using Expert Wisdom and Research to Frame Educational Practice - Kathy Smith; Nicoleta Maynard; Amanda Berry; Tanya Stephenson; Tabetha Spiteri; Deborah Corrigan; Jennifer Mansfield; Peter Ellerton; Timothy Smith (MDPI AG, 2022)
Developing teacher knowledge, skills, and confidence in Science, Technology, Engineering, and Mathematics (STEM) education is critical to supporting a culture of innovation and productivity across the population. Such capacity building is also necessary for the development of STEM literacies involving the ability to identify, apply, and integrate concepts from STEM domains toward understanding complex problems, and innovating to solve them. However, a lack of visible models of STEM integration has been highlighted by teachers as a challenge to successfully implementing integrated STEM education in schools. Problem Based Learning (PBL) has been well-established in higher education contexts as an approach to learning in the STEM disciplines and may present an effective way to integrate knowledge and skills across STEM disciplines in school-based STEM education and support the development of students as capable, self-directed learners. However, if PBL is to effectively contribute to STEM education in schools and build teacher capacity to teach STEM, then this approach needs to be better understood. This paper aims to generate a set of principles for supporting a PBL model of STEM education in schools based on insights from the literature and expert focus groups of PBL professionals. Four principles of PBL emerged from the data analysis: (a) flexible knowledge, skills, and capabilities; (b) active and strategic metacognitive reasoning; (c) collaboration based on intrinsic motivation; and (d) problems embedded in real and rich contexts. The study outcomes provide evidence-informed support for teachers who may be considering the value of adopting a PBL approach in school-based STEM education.